THE PORTRAYAL OF VICTIMIZED CHARACTERS IN SHAKESPEARE AND ULUGBEK’S NARRATIVES - Nurulloeva Zarina (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis comparatively analyzes the representation of victimized characters in the works of Shakespeare and Ulugbek, as well as their socio-ethical significance. The aim of the research is to identify the poetic devices and conflict mechanisms that construct victimhood. The study employs narratological and comparative-typological approaches as its methodology. Its scientific novelty lies in the systematic examination of the dynamics of agency, guilt and empathy within the text through the portrayal of victimized characters.